Performance Writing - Branislav Jakovljević (Amfiteater)
While the emergence of new forms of performance writing in the 1960s and 1970s did not eliminate traditional forms of drama, they radically transformed the role of textuality in the theatre. This article argues that when liberated from the rules of dramatic writing and even syntax and grammar, performance writing brings an illocationary logic into textual production. The article concludes with a preliminary consideration of differences between experimental writing strategies and the latest text-generating AI.